Audiometric assessment in patients with carcinoma of the larynx (2000)
Audiometric assessment was carried out on twelve patients with advanced carcinoma of the larynx who were on admission on the Ear, Nose and Throat Ward of the University College Hospital, Ibadan, Nigeria between October 1995 and June 1996. The sharp dropping curve was the most common type of audiograph observed. Fifty percent of the patients had very sharp dropping curve at 200Hz, 33.3% had mild dropping curve at 4000Hz and 8000Hz while 16.7% had a flat curve within the social adequacy range. Implications of this in the treatment and rehabilitation of such patients is discussed.